Der p 23‐specific IgE response throughout childhood and its association with allergic disease: A birth cohort study. Issue 7 (11th July 2022) - Forchert, Leandra; Potapova, Ekaterina; Panetta, Valentina; Dramburg, Stephanie; Perna, Serena; Posa, Daniela; Resch‐Marat, Yvonne; Lupinek, Christian; Rohrbach, Alexander; Grabenhenrich, Linus; Icke, Katja; Bauer, Carl‐Peter; et al.
Abstract: Background: The Dermatophagoides pteronyssinus molecule Der p 23 is a major allergen whose clinical relevance has been shown in cross‐sectional studies. We longitudinally analysed the trajectory of Der p 23‐specific IgE antibody (sIgE) levels throughout childhood and youth, their early‐life determinants and their clinical relevance for allergic rhinitis and asthma. Methods: We obtained sera and clinical data of 191 participants of the German Multicentre Allergy Study, a prospective birth cohort. Serum samples from birth to 20 years of age with sIgE reactivity to Der p 23 in a customised semiquantitative microarray were newly analysed with a singleplex quantitative assay. Early mite exposure was assessed by measuring the average content of Der p 1 in house dust at 6 and 18 months. Results: Der p 23‐sIgE levels were detected at least once in 97/191 participants (51%). Prevalence of Der p 23 sensitisation and mean sIgE levels increased until age 10 years, plateaued until age 13 years and were lowest at age 20 years. Asthma, allergic rhinitis (AR) and atopic dermatitis (AD) were more prevalent in Der p 23‐sensitised children, including those with monomolecular but persistent sensitisation (11/97, 11%). A higher exposure to mites in infancy and occurrence of AD before 5 years of age preceded the onset of Der p 23 sensitisation, which in turn preceded a higher incidence of asthma. Conclusions: Der p 23 sensitisation peaks in late childhood and then decreases. It is preceded by early mite exposure and AD. Asthma and AR can occur in patients persistently sensitised to Der p 23 as the only mite allergen, suggesting the inclusion of molecular testing of Der p 23‐sIgE for subjects with clinical suspicion of HDM allergy but without sIgE to other major D.pt. allergens.